PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR BERBASIS LINGKUNGAN HIDUP UNTUK SISWA KELAS IV SDN 013 KARIMUN - tisrin maulina dewi; Muhiri Muhiri; raja mitha karina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to see the feasibility of the product developed in the form of an environmental-based picture storybook for grade four students. The subjects in this study were ten students at grade V. The type of research was research and development which was modified into seven steps, namely: (1) Data collection/planning (2) Product design (3) Product design validation (4) Product revision (5) Teacher response (6 ) Field trial (7) Data analysis. The instruments in this study were interviews with teachers and questionnaires given to design experts, material experts, homeroom teachers for grade IV and ten grade four students. The results of this study consisted of (1) Validation by design experts obtained a score of 4.22 in the